A novel method for joint optimization of the sailing route and speed considering multiple environmental factors for more energy efficient shipping. (15th November 2020) - Wang, Kai; Li, Jiayuan; Huang, Lianzhong; Ma, Ranqi; Jiang, Xiaoli; Yuan, Yupeng; Mwero, Ngome A.; Negenborn, Rudy R.; Sun, Peiting; Yan, Xinping
Abstract: Energy saving and emission reduction have attracted a great deal of attention in the maritime industry. The optimization of a ship's energy efficiency can reduce energy consumption and CO2 emissions effectively. However, most of the available studies only focus on either the sailing speed or route optimization, and the interaction between speed and route under the influence of multiple environmental factors was not accounted properly. In this paper, a novel joint optimization method of the sailing route and speed, which considers the interaction between route and speed as well as multiple environmental factors, is proposed to fully exploit the energy efficiency's potential. Moreover, a joint optimization model of the sailing route and speed, which is based on an energy consumption model that considers multiple environmental factors, is established. Next, a solution algorithm for the joint optimization model is investigated in order to achieve joint decision-making with regard to the sailing route and speed. Finally, a case study is conducted that demonstrates the effectiveness of the proposed method. The results show that the proposed method can achieve the optimal sailing route and speed under complex environmental conditions, as well as a reduction in fuel consumption and CO2 emissions of about 4%. Graphical abstract: A novel joint optimization method of the sailing route and speed, which considers the interaction between route and speed as well as multiple environmental factors, is proposed to fully exploit the energy efficiency's potential. Firstly, the energy efficiency data of a ship and the meteorological information are obtained. Subsequently, a joint optimization model of the sailing route and speed, which is based on an energy consumption model that considers multiple environmental factors, is established, through the analysis of the navigational environment data and the energy efficiency data of the ship. Finally, a novel joint optimization method of the sailing route and speed that considers the multiple environmental factors is proposed. The proposed optimization method can jointly determine the optimal sailing route and speed under various navigational environmental conditions. A case study is carried out to demonstrate the validity of this optimization method. Our results show that the proposed method can achieve the optimal sailing route and speed under complex environmental conditions, as well as a reduction in fuel consumption and CO2 emissions of about 4%. Image 1 Highlights: A joint optimization model of the sailing route and speed is established. A solution algorithm for the joint optimization model based on the PSO is investigated. A novel joint optimization method of the sailing speed and route is proposed. The proposed method can reduce ship energy consumption and CO2 emissions by 4%.